Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/ejp.1729
|View full text |Cite
|
Sign up to set email alerts
|

Facial expressions of pain in daily clinical practice to assess postoperative pain in children: Reliability and validity of the facial action summary score

Abstract: Background: Behavioural pain scales are recommended to assess postoperative pain for children who are too young to use self-report tools. Their main limitation is underestimation of pain in the days following an intervention. Although relevant, facial expression is not used in daily clinical practice. This prospective study aimed to assess the validity and reliability of the Facial Action Summary Score (FASS), a fiveitem scale, to assess postoperative pain until hospital discharge in children <7 years. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…This is further supported by the high levels of accuracy and precision. It is worth mentioning that the cutoff threshold identified in this study is similar to that reported for the FASS using the FLACC as a comparator in postoperative pain [25]. The FASS and the NFCS-R are unidimensional tools, made up of 5 facial items.…”
Section: Principal Findingssupporting
confidence: 70%
See 3 more Smart Citations
“…This is further supported by the high levels of accuracy and precision. It is worth mentioning that the cutoff threshold identified in this study is similar to that reported for the FASS using the FLACC as a comparator in postoperative pain [25]. The FASS and the NFCS-R are unidimensional tools, made up of 5 facial items.…”
Section: Principal Findingssupporting
confidence: 70%
“…This is comparable to the NFCS-R, which contains 5 items (reduced from the 10 items that made up the original version of the tool) [ 23 , 24 ]. The Facial Action Summary Score (FASS), another unidimensional observational pain assessment tool, also includes 5 facial items [ 25 ]. The Faces, Legs, Arms, Cries, and Consolability (FLACC), multidimensional tool used for the assessment of procedural pain, has 5 domains; however, it uses an ordinal scoring system, such that the user is required to look for a variety of possible behaviors within each domain to determine absence or presence and intensity [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Observing facial expressions is part of the frequently used pain rating scales. Pain may be influenced by the procedures themselves, and patients subjected to unpleasant and painful procedures may have low observer rating scores [15].…”
Section: Introductionmentioning
confidence: 99%